Constitutional change in the United Kingdom - Forman, F. N. (Routledge, 2002)
The years since New Labour came to power in 1997 have seen changes to the British institutions of political power on an unprecedented scale. The reforms have been widespread, ranging from devolution of power in Scotland, Wales and Northern Ireland, to the reform of the House of Lords and the changing role of the Monarchy. This book is the first to examine these changes collectively and in detail, placing each in its historical context, analysing problems, solutions and what the future holds for this ambitious period of reforms. The book is comprehensive in coverage, and accessibly writt.